HTNV Sensitizes Host Toward TRAIL-Mediated Apoptosis—A Pivotal Anti-hantaviral Role of TRAIL - Chen, Qing-Zhou; Wang, Xin; Luo, Fan; Li, Ning; Zhu, Ni; Lu, Shuang; Zan, Yu-xing; Zhong, Chao-Jie; Wang, Mei-Rong; Hu, Hai-Tao; Zhang, Yong-Zhen; Xiong, Hai-Rong; et al. (Frontiers in Immunology, 2020)
Hantaviruses can cause hemorrhagic fever with renal syndrome (HFRS) in Eurasia and have led to public health threat in China. The pathogenesis of HFRS is complex and involves capillary leakage due to the infection of vascular endothelial cells. Accumulating evidence has demonstrated that hantavirus can induce apoptosis in many cells, but the mechanism remains unclear. Our studies showed that Hantaan virus (HTNV) infection could induce TNF-related apoptosis-inducing ligand (TRAIL) expression in primary human umbilical vein endothelial cells (HUVECs) and sensitize host cells toward TRAIL-mediated apoptosis. Furthermore, TRAIL interference could inhibit apoptosis and enhance the production of HTNV as well as reduce IFN-β production, while exogenous TRAIL treatment showed reverse outcome: enhanced apoptosis and IFN-β production as well as a lower level of viral replication. We also observed that nucleocapsid protein (NP) and glycoprotein (GP) of HTNV could promote the transcriptions of TRAIL and its receptors. Thus, TRAIL was upregulated by HTNV infection and then exhibited significant antiviral activities in vitro, and it was further confirmed in the HTNV-infected suckling mice model that TRAIL treatment significantly reduced viral load, alleviated virus-induced tissue lesions, increased apoptotic cells, and decreased the mortality. In conclusion, these results demonstrate that TRAIL-dependent apoptosis and IFN-β production could suppress HTNV replication and TRAIL treatment might be a novel therapeutic target for HTNV infection.